CYPRUS 2003 EU Accession and Failed UN initiatives - Coufoudakis, Van (Études helléniques / Hellenic Studies, 2003)
This article describes the background and negotiations leading to Kofi Annan's ultimate plan. The author highlights the role played by key players including Kofi Annan, Alvaro de Soto, Hannay, Holbrooke, Clerides and Denktash, among others. He outlines how the Annan plan would not have succeeded as hoped and how the recently signed by the Republic of Cyprus EU Accession Treaty affects hopes for a settlement of the Cyprus problem.